1997
DOI: 10.1016/s0042-6989(97)00095-3
|View full text |Cite
|
Sign up to set email alerts
|

Fillers and spaces in text: The importance of word recognition during reading

Abstract: Current theories of reading eye movements claim that reading saccades are programmed primarily on the basis of information about the length of the upcoming word, determined by low-level visual processes that detect spaces to the right of fixation. Many studies attempted to test this claim by filling spaces between words with various non-space symbols (fillers). This manipulation, however, confounds the effect of inserting extraneous characters into text with the effect of obscuring word boundaries by filling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…The spaces between words in alphabetic scripts provide exactly this information. Removing space information not only reduces reading speed significantly (Epelboim, Booth, Ashkenazy, Taleghani, & Steinman, 1997;Epelboim, Booth, & Steinman, 1994;Rayner et al, 1998;Rayner & Pollatsek, 1996), but more importantly, the PVL curve decreases sharply and linearly from the beginning to the end of the word, because it presumably impedes the identification of the beginning and end of a given word which is necessary to delineate the saccade target (Rayner et al, 1998;Rayner & Pollatsek, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The spaces between words in alphabetic scripts provide exactly this information. Removing space information not only reduces reading speed significantly (Epelboim, Booth, Ashkenazy, Taleghani, & Steinman, 1997;Epelboim, Booth, & Steinman, 1994;Rayner et al, 1998;Rayner & Pollatsek, 1996), but more importantly, the PVL curve decreases sharply and linearly from the beginning to the end of the word, because it presumably impedes the identification of the beginning and end of a given word which is necessary to delineate the saccade target (Rayner et al, 1998;Rayner & Pollatsek, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, natural language research in psychology suggests that this is the wrong choice. For example, a study by Epelboim et al [6] considered the effect of the type of space filler on word recognition. They found that replacing spaces with Latin letters, Greek letters, or digits had a negative impact on reading.…”
Section: Introductionmentioning
confidence: 99%
“…Current theories of eye movements while reading assert that reading saccades (essentially where the eye lands when one is reading) are programmed primarily on the basis of information about the length of the upcoming word. This is determined by lowlevel visual processes that detect spaces to the right of fixation point [6].…”
Section: Introductionmentioning
confidence: 99%
“…In psychology research, Epelboim et al [12] conducted a study on the effect fillers have on reading time. Spaces between words are filled with different fillers: Latin and Greek letters, digits and shaded boxes.…”
Section: Related Workmentioning
confidence: 99%
“…The main task of the study remains the same as Binkley's, which is to pick the correct identifier from a group of four closely related, although different, identifier names. Results from eye tracking studies done in the domain of cognitive psychology [12,21] on reading un-spaced text imply that camel-cased identifiers should be more difficult to read compared to underscored identifiers. We believe that replicating the experiment using an eye tracker will add to the empirical evidence as to which style is faster and more accurate for comprehension.…”
Section: Introductionmentioning
confidence: 99%